HUBUNGAN ANTARA SELF EFFICACY DENGAN SUBJECTIVE WELL BEING PADA MAHASISWA BARU DI ETNIS TIMUR (IKMASTI) DI SALATIGA - Junaldi Bistolen; M Erna Setianingrum (Jurnal Basicedu, 2020)
Education is one of the important needs for people in living their lives. In the eastern region of NTT, education has started to become a top priority, many students choose to migrate to get a good education, but in the transition and overseas life when students are unsure of their abilities, it will have an impact on student life satisfaction in overseas areas  and lectures. This research aims to determine the relationship between self efficacy and subjective well-being in ethnic Ikmasti students in Salatiga, this study uses a sampling technique saturated with participants involved 60 people taken from Ikmasti students. Data collection was carried out for 1 week. The self efficacy variable was composed by Albert Bandura (1997) consisting of 40 items and subjective well-being Diener (1984) and Watson & Telegen (1988) consisting of 40 items. The method used in this study for data collection uses a scale method, namely the scale of self efficacy and subjective well-being scale. Data analysis using product moment correlation analysis techniques and the results obtained by correlation coefficient 0.525 with sig.  = 0,000 (p ˂ 0,001). The results showed a positive relationship between self-efficacy and subjective well-being in ethnic Ikmasti students in Salatiga.